(untitled) (Journal of Economic Research & Business Administration, 2018)
The problem of ensuring food security remains one of the most important in both political and socio-economic relations. It should be one of the most important priorities in the national security system, since without a reliable supply of food the country is not able to be independent of other states. Therefore, in its general form, it forms the vector of movement of any national food system to an ideal state. Economic development of the state, its potential, stability and position in the modern world are determined by the ability to ensure the country’s food security. This article analyzes the state of food security based on the following indicators: gross agricultural production, production of the main agricultural products, the structure of foreign trade in food, the level of food independence and economic accessibility.The state should serve as a basis for social stability, which ensures the existence of the state itself. In this regard, it is necessary to exclude the country’s dependence on imported supplies, to ensure the development of its own food production; creation of a balanced structure of exports and imports.